REVITALIZATION OF MALAY LANGUAGE IN EDUCATIONAL ENVIRONMENT: A CASE STUDY OF YANYAWIT SCHOOL, THAILAND - Iswandi, Iswandi; Islahuddin; Mahamadaree Waeno; Zahri, Mustafa; Saputra, Ilham; Ratnawilis; Alfianti (Amanah Publishing, 2025)
This study aims to examine the Malay language revitalization efforts within the educational environment at Yanyawit School, Thailand. Malay, as one of the ethnic languages ​​​​living in Southern Thailand, is experiencing a decline in function and use, especially among the younger generation. Using a qualitative approach with a case study method, this study explores the strategies implemented by educational institutions in maintaining and developing Malay as part of the local cultural identity. Data were collected through observation, interviews with teachers and students, and analysis of learning documents. The results show that Yanyawit School has undertaken various revitalization efforts, including through the integration of Malay into the curriculum, extracurricular activities in Malay, and community involvement in language preservation. These findings emphasize the importance of the role of schools as agents of local language preservation and provide recommendations for the development of multilingual education policies in multiethnic regions.